Pengaruh Metode Latihan Sirkuit terhadap Keterampilan Memanah - Arisman Arisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aimed to determine the effect of training using the circuit training method on archery skill of the extracurricular students of the Auladi Islamic Primary School Palembang. This type of research was involved in the category of quasi-experimental research. The population of this study was 35 people, while the sample was determined by purposive sampling so that a sample of 24 male students was obtained. The data was obtained through basic technique test. While data analysis used independent sample t- test. The result of data analysis showed that training using the circuit training method significantly affected the improvement of archery skill, where tvalue ﹥ t table = 4.49> 1.714. Conclusion, the method of circuit training effectively had a positive influence on archery skill. Keywords:Circuit Training, Metho, Archery